1986
DOI: 10.1152/ajprenal.1986.250.2.f364
|View full text |Cite
|
Sign up to set email alerts
|

Frequency domain analysis of renal autoregulation in the rat

Abstract: The frequency response of renal blood flow was estimated to test our suggestion that autoregulation had one fast and one slow component. Arterial pressure was varied periodically by a pump connected to the distal aorta or aperiodically by stimulating atrial fibrillation. There was only one regulatory mechanism, corresponding to the slow component seen earlier. Two apparent regulators were seen when pressure was measured far from the renal artery (right common carotid), rather than near (superior mesenteric). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 0 publications
4
14
0
Order By: Relevance
“…Results are also the same whether calculated from spontaneous fluctuations of pressure (2,3,9,18,62,116,122,147,161,205,207), from experimentally enhanced variations (41), or from forced oscillations (37,79,81,179,205,206,213). Other studies reported comparable results for parts of the spectrum, although their frequency range was either too high to include TGF (126,159), too low to embrace MR (213), or lower than both mechanisms (126).…”
Section: Transfer Function Analysissupporting
confidence: 61%
“…Results are also the same whether calculated from spontaneous fluctuations of pressure (2,3,9,18,62,116,122,147,161,205,207), from experimentally enhanced variations (41), or from forced oscillations (37,79,81,179,205,206,213). Other studies reported comparable results for parts of the spectrum, although their frequency range was either too high to include TGF (126,159), too low to embrace MR (213), or lower than both mechanisms (126).…”
Section: Transfer Function Analysissupporting
confidence: 61%
“…Simultaneous measurements of MAP from the carotid artery and the aorta indicate that there is no significant difference in the MAP recorded from the 2 sites, suggesting that the pressure wave does not significantly dissipate as it travels to the lower aorta. 11 In the telemetry studies, the MAP recorded by the aortic versus the carotid telemetry probes was consistently lower; this, however, is likely due in part to the small number of animals in the abdominal aorta group and/or the disruption due to the more invasive abdominal surgery and the presence of the probe in the gut.…”
Section: Discussionmentioning
confidence: 89%
“…Studies by Cupples, Bidani, Griffin and colleagues reported the resonance frequency of the myogenic mechanism to be 0.23-0.25 Hz in conscious rats (886,1193), compared with the general finding of 0.18 -0.21 Hz in rats anesthesized with isofluorane or barbiturates (109, 297, 499,597,749,1274,1358,1569,1570,1572). There were similar responses during anesthesia with thiobutabarbital (597, 1274) and pentobarbital (297, 749), but halothane slowed the operating frequency of the myogenic mechanism in SD, SHR, and WKY rats to 0.10 -0.15 Hz (230, 289, 631, 886, 1636).…”
Section: Kinetics Of the Myogenic Responsementioning
confidence: 93%
“…Kidneys normally exhibit oscillations in microvascular tone. Transfer function analyses of the gain of renal vascular admittance (the reciprocal of impedance and similar to steady-state conductance that is the reciprocal of resistance) to spontaneous or imposed changes in RPP can distinguish between autoregulatory components in the frequency domain (19,230,297,629,631,722,971,1274,1357,1358,1563,1569,1570). This has been investigated in conscious dogs (753,755,760,1618), mice (668), rabbits (722), and rats (927,1182,1183,1376).…”
Section: Dynamics Of Autoregulatory Responsesmentioning
confidence: 99%